Community medicine in India - Which way forward? - Anand Krishnan (Wolters Kluwer Medknow Publications, 2016)
Today, the Community Medicine professionals in India feel both "confused" and "threatened" by the mushrooming of schools of public health and departments of family medicine. The phenomenon of identity crisis and low-self esteem is not a recent one, nor is it restricted to India. The disciplines of community medicine and public health have evolved differently and despite some overlaps have differences especially in the need for clinical training. The core of the issue is that while the community medicine fraternity is keen to retain its clinical tag, what differentiates it from clinicians is the use of public health approach. I believe the strength of community medicine is that it bridges the gap between traditional fields of public health and clinical medicine and brings community perspective into health. The perceived threat from non-medical persons led public health is largely a result of us undervaluing our strength and our inability to foster partnership on equal footing with non-clinicians. While departments of community medicine have a fully functional rural or urban field practice area used for training at primary level care, these can serve as an excellent platform for training in secondary level care required for family medicine. National needs dictate that all three disciplines are required for improvement of population health, whether these are housed together or separately can be left to individual institutions to decide as long as they enable collaborations between them. We need to strengthen community medicine and market it appropriately to ministries of health.